PENERAPAN METODE RUNGE-KUTTA ORDE 4 DALAM ANALISIS RANGKAIAN RLC - Rika Favoria Gusa (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2014)
The existence of inductor and capacitor in RLC circuit without source, at least, creates system that has characteristic of second order differential equation. Differential equation can be solved using 4th order Runge-Kutta method. RLC circuits without source that have same configuration yet different elements value will give different responses. It makes RLC circuit analysis become difficult. The solving steps of the equation of RLC circuit without source that is a second order differential equation begun with making 2 first order differential equations based on the RLC circuit equation. The next step is typing solving steps using 4th order Runge-Kutta method based on 2 first order differential equationsin Matlab to get the natural response graphic of series RLC circuit and parallel RLC circuit in a short time. By solving the equation of series RLC circuit without source and parallel RLC circuit without source, known that the using of the 4th order Runge-Kutta method in RLC circuit analysis give results (natural response) with high accuracy compared with the exact values of natural response. For the parallel RLC circuit discussed, the highest error is 0,0023 (0,23%). For the series RLC circuit discussed, there is no error.